Socio-Economic Rationality Towards Interest and Access To Education: A Study Of Teenage Fishermen In The Pongok Islands - Tania Januarti; Shakira Mahendra Putri; Berlian Birly Aeywaldy; Anis Anis; Amirah Tsania Khansa; Putra Pratama Saputra (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
This research analyzes the phenomenon of low educational participation among teenage fishermen in the Pongok Islands District, South Bangka Regency. As an archipelago with 95% of the population working as fishermen, this area faces significant problems related to teenagers who choose to work as fishermen instead of continuing their Education. This research uses a qualitative method with a case study approach, involving interviews with 20 teenage fishermen in Pongok Village and 20 teenage fishermen in Celagen Village, family members of teenage fishermen, as well as village equipment in Pongok Village and Celagen Village, and observation and documentation were carried out in Pongok Village and Celagen Village. Max Weber's theory of rationality, especially instrumental rationality, is used as a framework for analysis to understand the logic behind the teenager's decisions. Research results show that the decision of teenagers not to continue their Education is not a form of irrationality, but a rational choice based on socioeconomic considerations. The main factors that influence this decision include, (1) the family's high economic dependence on the fishing sector with fluctuating income, (2) geographical isolation that creates limited access to adequate educational facilities, (3) urgent economic needs that force teenagers to help make a living, and (4) local cultural values that have not entirely placed formal Education as a top priority, through Weber's instrumental rationality theory that emphasizes goal-oriented social actions where individuals make conscious choices based on considerations of efficiency, profit, and the most beneficial consequences for themselves. In this study, instrumental rationality theory can be used to understand how teenage fishermen and their families make decisions related to Education. These considerations are not solely based on moral values or traditions, but on rational calculations of economic benefits and educational costs. The choice of teenage fishermen to drop out of school reflects a form of instrumental rationality influenced by the family's socioeconomic conditions. When Education is considered not to provide short-term benefits compared to the results of going to sea, then some families prefer their children to work to increase household income, reinforced by structural obstacles such as limited high schools, a lack of educators, and difficult access to transportation between islands. Focusing on the rationality of teenagers who drop out of school and choose to work as fishermen, this study highlights not only the lack of access to Education but also the existence of more rational choices, as perceived by those teenagers, leading them to drop out of school and believe that working is more profitable.